Factors Contributing to Divorce in Ghana: An Exploratory Analysis of Evidence From Court Suits - Osafo, J.; Asante, K.O.; Ampomah, C.A.; Osei-Tutu, A. (Taylor & Francis Group, 2021)
In Ghana, some divorce cases are conducted through the courts, and the reasons for such cases are important to gauge the factors that account for the dissolution of marriages in Ghana. This study was conducted to explore in-depth, the factors that lead to divorce using court suits in Ghana. Data were obtained from 30 lawsuits consisting of 11 men and 19 women with an age range of 29–71 years. Reasons for marital dissolution were assembled from a 10-year period (2007–2017) cases of divorce from the Greater Accra Region of Ghana. Conventional content analysis identified six main factors as possible reasons for divorce: infidelity, abuse, financial support, intimacy, financial problems, third-party intrusion and gender-role ideology. Men were likely to seek for divorce at an older age compared to women. Women attributed reasons for divorce to lack of respect from the husband and gender-role ideology. Our findings underscore the need for pre-marital counseling psychologists to help would-be couples address pertinent issues which could lead to distress and ultimately divorce in their marriages.
Research Article
Keywords: Divorce; court suits; gender-role ideology; qualitative; Ghana